IMPACT OF HUMAN CAPITAL ON THE PERFORMANCE (QUALITY OF PUBLICATIONS) OF RESEARCH INSTITUTES IN INDIA- AN EMPIRICAL STUDY - Ajay Kumar, Saini; Harpreet Singh, Grewal; Harish Kumar, Singla (Journal of Human Capital Development (JHCD), 2016)
The purpose of the paper is to see the impact of Knowledge, skills, Innovation & creative ability and human capital as a whole on the quality of publications in research institutions in India. The quality of publication is defined as number of SCI publications in last five years and Knowledge, skills, Innovative &Creative Ability and human capital is measured through a comprehensive research questionnaire on 5 point scale. The responses from 119 scientists across various research institutions were collected and analyzed using Structural Equation model. The results of the study show that Knowledge, skills and Innovative and creative capability and human capital as a whole have a positive significant impact on the quality of publications in India. Key Words: human capital, intellectual capital, knowledge, R&D, performance